Methionine restriction in cancer: a dietary insight for therapy - Tian, Xing; Zhu, Gengjun; Zhang, Yuhua; Liu, Ning (Frontiers in Nutrition, 2026)
BackgroundMethionine, one of the essential amino acids that needs to be obtained through protein-rich diet, provides important sulfur elements for the human body, which is crucial for protein synthesis, antioxidant and metabolic regulation. Many tumors develop a metabolic dependency due to the lack of a working methionine salvage pathway, which can be targeted by methionine restriction (MR).ResultsThe core mechanism of MR lies in disrupting one-carbon metabolism and epigenetic regulation that rely on methionine, depleting the crucial metabolite S-adenosylmethionine (SAM), thereby inhibiting histone/DNA methylation, disrupting redox homeostasis, and ultimately inducing cell cycle arrest and apoptosis. Substantial evidence indicates that MR, achieved by specific metabolic enzyme inhibitors or diet with special formulations, can intervene in tumor progression from a metabolic standpoint. Additionally, combining methionine restriction with existing treatments can achieve satisfactory outcomes in the clinical management of various tumors.ConclusionThis article provides insights into the research and its translational potential of methionine restriction as a promising strategy for cancer treatment, with the emphasis on the contributions that advance the field and better serve the clinical research community.